Theoretical and Methodological Approaches to Definition of Concept of Constitutional Right for Strike - KOLOMOIETS, Yuliia O.; BONYAK, Valentyna O.; KHOROSHILOVA, Irina O. (Journal of Advanced Research in Law and Economics; Vol 9 No 7 (2018): JARLE Volume IX Issue 7(37) Winter 2018DO - 10.14505//jarle.v9.7(37).18, 2019)
The article deals with existing theoretical and methodological approaches to the definition of the concept ‘constitutional right to strike’. On the basis of their analysis the authors have reasoned that the constitutional right to strike is a socially determined, determined by the objective law norms the measure of possible (permissible) behavior of able-bodied subjects as an authorized party to the constitutional-legal relations, consisting in the temporary collective voluntary termination of work and provided to protect their own and general socio-economic rights and interests of the labor collective, provided by the behavior of the obliged party and guaranteed by the state. They have proved that the essence of the strike is the ability of each employee to protect both their own and collective social and economic rights and interests. The right to strike is a social regulator of conflict situations when other possibilities for their solution are exhausted. The authors have determined that this right is considered to be mixed – is being realized both individually and collectively.